Water as a nanostructured material - Sergentu, Vladimir (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2016)
A nanostructured disordered ice Ih fraction in a water environment is theoretically investigated. The disordered ice fraction is taken into account as a nanocomposite consisting of a substance and a vacuum. The pattern of interaction between electrical charges considerably changes and thus leads to the formation of stable ice clusters that are consolidated by bound charges.